Inhibition of Auxin-induced Deoxyribonucleic Acid Synthesis and Chromatin Activity by 5-Fluorodeoxyuridine in Soybean Hypocotyl - Holm, Robert E. (1971)
Rootless soybean (Glycine max) seedlings were used as a test system to examine the action of auxin on chromatin-directed RNA synthesis. Chromatin from the basal tissue of rootless seedlings (both control and auxin-treated) had RNA synthetic capacity similar to that of chromatin from comparably treated intact seedlings. When DNA synthesis normally induced in the basal tissue by auxin was blocked in the rootless seedlings by 5-fluorodeoxyuridine, the auxin enhancement of chromatin activity was inhibited 70%. This level was still three times the control level, indicating that auxin influenced the synthetic activity of existing DNA template. Experiments with Escherichia coli RNA polymerase revealed that chromatin from both auxin- and auxin plus 5-fluorodeoxyuridine-treated tissue saturated at higher levels than chromatin from control tissue.